Ictal Lid Movements: Blinks and Lid Saccades. (3rd September 2021) - Pyatka, Nataliya; Gajera, Prasannakumar; Fernandez-Bacavaca, Guadalupe; Lhatoo, Samden D.; Shaikh, Aasef G.
ABSTRACT: Two types of lid movements, blinks and lid saccades, have discrete kinematic properties and physiology. These differences are reflected in distinct phenomenology of disorders affecting their neural substrate. Proof of this principle was seen in two patients, one with parietal lobe epilepsy and the other with temporal lobe epilepsy. The lid movements in the patient with parietal lobe epilepsy were rhythmic, yoked, and had a rapid upward component that instantaneously followed a slow downward drift. These cyclic movements strikingly resembled nystagmus, but unlike typical eye nystagmus, the rapid upward component was pathological and seemed to involve a saccadic mechanism. We suggest the terms "ictal lid saccades" or "ictal lid nystagmus" to describe such a phenomenon. In contrast, the patient with temporal lobe epilepsy had ipsilateral lid movements with rapid downward trajectories resembling reflex or spontaneous blinks. The term "ictal blink" is appropriate for this phenomenon.